PERENCANAAN RUNWAY END SAFETY AREA DI THRESHOLD 30 BANDAR UDARA TRUNOJOYO SUMENEP - Adelia Pramitasari (Approach : Jurnal Teknologi Penerbangan, 2021)
Trunojoyo Airport which is located on Jl. Raya Trunojoyo Airport No. 01, Sumenep, East Java which has important functions for transportation, tourism, economy and trade. Sumenep Airport needs to meet aviation safety standards in accordance with the rules of Annex 14, ICAO (Indonesian Civil Aviation Organization) and KP 326 of 2019. In order to create optimal flight security and safety, one of the things that needs to be fulfilled is the existence of a Runway End Safety Area (RESA) that is in accordance with aspects of operational feasibility. This plan takes into account operational feasibility assessments such as dimensions, slope and surface condition of the RESA. To form a RESA slope in accordance with existing regulations, it is necessary to use cut and fill work with the manual method and use software called PCLP which is supported by Microsoft Excel and AutoCAD applications. In planning the RESA threshold 30 at Trunojoyo Airport, it will be planned with a size of 90 x 60 meters. As well as the slope that is in accordance with regulations and meets operational feasibility, namely the transverse slope with a percentage of 2.5% and the percentage of longitudinal slope of 0.8%. In the cut and fill work, it is possible to obtain an excavation volume of 11,077,0502 m3 with a planned budget of Rp 1,253,562,000